//Affekte / Affects : Kunstpalais Erlangen. - Emmert, Claudia; Neddermeyer, Ina; Splint, Marianne; Hoenjet, Frank; Leemans, Koen; Van de Voorde, Anne (Erlangen ; Helmond ; Mechelen : Kunstpalais Erlangen : Gemeentemuseum Helmond : Cultuurcentrum Mechelen, 2015)
Ader, Bas Jan ; Altindere, Halil ; Arnold, Robert ; Arrhenius, Lars ; Asselberghs, Herman ; Bartana, Yael ; Cytter, Keren ; Foighel Brutmann, Sirah ; Efrat, Eitan ; Colson, Vaast ; De Bruyckere, Berlinde ; Gaillard, Cyprien ; De Gruyter, Jos ; Thys, Harald ; Hauser, Koen ; Koizumi, Meiro ; van Lierop, Marilou ; Mik, Aernout ; Olaf, Erwin ; Opton, Suzanne ; van der Ploeg, Adriaan ; Sierra, Santiago ; ter Heijne, Mathilde ; Trecartin, Ryan ; Viola, Bill ; Watanabe, Tomoya ; Wauman, Andy
Affekte / Affects, Kunstpalais Erlangen, Erlangen, 04.04. - 08.06.2014 ; Emoties (in de hedendaagse kunst), Gemeentemuseum Helmond, Helmond, 12.10.2014 - 11.01.2015 ; Mixed Emotions / Gemengde gevoelens, Cultuurcentrum Mechelen, Mechelen, 14.02. - 26.04.2015
boek